Decoding perineuronal net glycan sulfation patterns in the Alzheimer's disease brain. Issue 5 (5th September 2021) - Logsdon, Aric F.; Francis, Kendra L.; Richardson, Nicole E.; Hu, Shannon J.; Faber, Chelsea L.; Phan, Bao Anh; Nguyen, Vy; Setthavongsack, Naly; Banks, William A.; Woltjer, Randy L.; Keene, C. Dirk; Latimer, Caitlin S.; et al.
Abstract: The extracellular matrix (ECM) of the brain comprises unique glycan "sulfation codes" that influence neurological function. Perineuronal nets (PNNs) are chondroitin sulfate‐glycosaminoglycan (CS‐GAG) containing matrices that enmesh neural networks involved in memory and cognition, and loss of PNN matrices is reported in patients with neurocognitive and neuropsychiatric disorders including Alzheimer's disease (AD). Using liquid chromatography tandem mass spectrometry (LC‐MS/MS), we show that patients with a clinical diagnosis of AD‐related dementia undergo a re‐coding of their PNN‐associated CS‐GAGs that correlates to Braak stage progression, hyperphosphorylated tau (p‐tau) accumulation, and cognitive impairment. As these CS‐GAG sulfation changes are detectable prior to the regional onset of classical AD pathology, they may contribute to the initiation and/or progression of the underlying degenerative processes and implicate the brain matrix sulfation code as a key player in the development of AD clinicopathology.